Rhabdomyomatous (Mesenchymal) Hamartoma Presenting as Haemangioma on the Upper Lip: A Case Report with Immunohistochemical Analysis and Treatment with High-Power Lasers - Aluana Dal Vechio; Edgar Nakajima; Décio Pinto; Luciane Hiramatsu Azevedo; Dante A. Migliari (Case Reports in Dentistry)
Rhabdomyomatous hamartoma is a rare disease that occurs predominantly in the skin. This paper describes a congenital lesion in a 17-year-old male, who came to our clinic presenting a circumscribed swelling involving the oral mucosa and vermillion border of the upper lip, purplish in color, and blanching under pressure. The patient reported that he had had lesion since his birth. A clinical diagnosis was of congenital haemangioma, and the patient was treated by photocoagulation using diode laser. When the lesion became smaller, by having its blood content reduced, the upper portion of the lesion was sliced off with CO2 laser and the tissue was sent for microscopic analysis. Histopathological examination showed an oral mucosa fragment with proliferation of striated muscle bundles admixed with small blood vessels, collagen, and nerve fibres. A supplementary analysis with immunohistochemistry demonstrated positivity for desmin, HHF35, smooth muscle actin, S-100, and CD34. Based on these findings, the lesion was diagnosed as rhabdomyomatous hamartoma. The aesthetic result has been very satisfactory after a 14-month followup.